Bladder cancer. Issue 10 (October 2022) - Stroman, Luke; Issa, Rami
Abstract: Bladder cancer is the second most common malignancy affecting the urinary tract and represents 3% of all cancer deaths in the United Kingdom. The most common presentation is visible haematuria which accounts for 85% of cases. Initial evaluation utilizes white light flexible cystoscopy and upper urinary tract imaging, through ultrasound or CT urography. Alternatives to white light cystoscopy include photodynamic diagnosis and narrow-band imaging which may improve detection of tumours. Initial treatment is with transurethral resection of the bladder tumour (TURBT). En-bloc resection using either laser or electrocautery shows promise in improving the quality of transurethral resection. For patients with muscle-invasive bladder cancer, robot-assisted radical cystectomy has been shown to be oncologically equivalent to open radical cystectomy with recent evidence showing benefit reducing pain and in inpatient stay. Bladder preservation treatment in muscle-invasive cancer is trimodal therapy utilizing transurethral resection and chemoradiotherapy in selected patients. Management of locally advanced and metastatic disease has rapidly advanced through the use of systemic immunotherapy agents targeting the PD-L1/PD-1 axis.